Anti-SARS-CoV-2 antibody response after 2 and 3 doses of BNT162b2 mRNA vaccine in patients with lymphoid malignancies. (June 2022) - Gressens, Simon B.; Fourati, Slim; Le Bouter, Anne; Le Bras, Fabien; Dupuis, Jehan; Hammoud, Mohammad; El Gnaoui, Taoufik; Gounot, Romain; Roulin, Louise; Belhadj, Karim; Haioun, Corinne; Gallien, Sébastien; et al.
Abstract: Objectives: COVID-19 patients affected by haematological malignancies have a more severe course of the disease and higher mortality, prompting for effective prophylaxis. The present study aims to evaluate the humoral response after mRNA vaccination as well as the impact of a third vaccine dose in patients with lymphoid malignancies. Methods: We conducted a single-centre study, evaluating the serological responses of mRNA vaccination amongst a cohort of 200 patients affected by lymphoid malignancies after two or three doses using an industrial SARS-CoV-2 serology assay for anti-receptor binding domain (RBD) Spike IgG detection and quantification. Results: Among patients with plasma cell disorders, 59 of 96 (61%) had seroconversion (anti-RBD >50 AU/mL), and recent anti-CD38 therapies were associated with lower serological anti-RBD IgG concentrations (median IgG concentration 137 (IQR 0–512) AU/mL vs. 543 (IQR 35–3496) AU/mL; p < 0.001). Patients with B-cell malignancies had a lower seroconversion rate (20/84, 24%) mainly due to the broad usage of anti-CD20 monoclonal antibodies; only 2 of 53 (4%) patients treated by anti-CD20 antibodies during the last 12 months experienced a seroconversion. A total of 78 patients (44 with plasma cell disorders, 27 with B-cell malignancies, and 7 with other lymphomas) received a third dose of vaccine. The seroconversion rate and antibody concentrations increased significantly, especially in patients with plasma cell disorders, where an increment of anti-RBD IgG concentrations was observed in 31 of 44 (70%) patients, with an anti-RBD concentration median-fold increase of 10.6 (IQR 2.4–25.5). Its benefit in B-cell malignancies is uncertain, with only 2 of 25 (8%) patients having seroconverted after the vaccine booster, without increased median antibody concentration. Discussion: A third mRNA vaccine dose significantly improved humoral responses among patients with plasma cell disorders, whereas the effect was limited among patients with B-cell malignancies. Graphical abstract: Image 1